Effect of sheep breed on milk yield and composition in the geographical area of production of Nisa PDO cheese - Marques M.R.; Belo A.T.; Pereira E.A.; Martins A.P.L.; Barata A.; Belo C. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
The traditional Portuguese cheeses have been produced for a long time from autochthonous sheep breeds' milk, namely Saloia and Merino breeds in the geographical area of PDO Nisa cheese. Aiming to improve farm profitability, exotic breeds, mainly Assaf, were introduced in the region. The objective of the project was to investigate the effect of sheep breed, lambing season and phase of lactation on milk production, milk composition and technological properties for cheese production. Farms rearing Lacaune, Assaf, Saloia, Merino and Serra da Estrela sheep, have been studied in two winter/spring and summer lactations. This work reports the milk yield and the chemical properties. Exotic breeds produced more milk than the Portuguese ones and it was observed that late parturition in winter and summer has a detrimental effect on milk production. The milk from the Merino breed has the highest fat, protein and total solid contents. However, considering milk production, the exotic breeds produced more total solids, an important factor for cheese yield.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)